THE USE OF VIRTUAL REALITY (VR) / AUGMENTED REALITY (AR) AS LEARNING MEDIA IN SCIENCE AND SOCIAL STUDIES SUBJECTS IN ELEMENTARY SCHOOL - Devi Rahmiati (STKIP Subang, 2024)
This study aims to identify the use of Virtual Reality (VR) and Augmented Reality (AR) as educational media in the Science and Social Studies (IPAS) subjects at the elementary school level. VR and AR are considered technologies that can enhance students' learning experiences by providing interactive visualizations and immersive learning environments. These media allow students to better understand abstract concepts in IPAS through in-depth visual simulations and explorations. The study utilizes a literature review method, using the keyword